2017
DOI: 10.1002/chem.201703352
|View full text |Cite
|
Sign up to set email alerts
|

(CF3)3Au as a Highly Acidic Organogold(III) Fragment

Abstract: The Lewis acidity of perfluorinated trimethylgold (CF ) Au was assessed by theoretical and experimental methods. It was found that the (CF ) Au unit is much more acidic than its nonfluorinated analogue (CH ) Au, and probably sets the upper limit of the acidity scale for neutral organogold(III) species R Au. The significant acidity increase on fluorination is in line with the CF group being more electron-withdrawing than CH . The solvate (CF ) Au⋅OEt (1) is presented as a convenient synthon of the unsaturated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 139 publications
3
38
0
Order By: Relevance
“…The higher the oxidation degree (for instance, Au(III) vs. Au(I)) the more acidic the Lewis acid; see, for instance, the complex (CF 3 ) 3 Au• • • pyridine [63]. We cited Legon in a 2014 paper [64] The higher the oxidation degree (for instance, Au(III) vs.…”
Section: Regium Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the oxidation degree (for instance, Au(III) vs. Au(I)) the more acidic the Lewis acid; see, for instance, the complex (CF 3 ) 3 Au• • • pyridine [63]. We cited Legon in a 2014 paper [64] The higher the oxidation degree (for instance, Au(III) vs.…”
Section: Regium Bondsmentioning
confidence: 99%
“…We cited Legon in a 2014 paper [64] The higher the oxidation degree (for instance, Au(III) vs. Au(I)) the more acidic the Lewis acid; see, for instance, the complex (CF3)3Au•••pyridine [63]. We cited Legon in a 2014 paper [64] In 2019, several papers were published on regium bonds, from which we have selected the following four Reference works [65][66][67][68].…”
Section: Regium Bondsmentioning
confidence: 99%
“…Non‐reductive ionic dissociation of F − is highly endergonic: Δ G 0 =74.5 kcal mol −1 . This value is the reverse of the FIA corresponding to the (CF 3 ) 3 Ag fragment, which thus appears as a molecular Lewis acid of considerable strength . The overall thermodynamic balance for the concerted reductive elimination of CF 4 or C 2 F 6 is strongly favored (Δ G 0 <−52 kcal mol −1 ).…”
Section: Methodsmentioning
confidence: 93%
“…The resultsa re shown in SchemeS1( SI) and summarized in Scheme3.N on-reductive ionic dissociation of F À is highly endergonic: DG 0 = 74.5 kcal mol À1 .This value is the reverse of the FIA corresponding to the (CF 3 ) 3 Ag fragment, which thus appears as am olecular Lewis acid of considerable strength. [28] The overall thermodynamic balance for the concertedr eductivee limination of CF 4 or C 2 F 6 is strongly favored (DG 0 < À52 kcal mol À1 ). These concerted processes,h owever,i nvolveh igh activation barriers (DG°% 40 kcal mol À1 )t hat might well hindert he occurrence of these single-step two-electronr eductions in favor of less energetically demandingp aths.…”
Section: Dedicatedtodrm Ilagros Tomµso Nthe Occasion Of Her 65th Birmentioning
confidence: 99%
“…Besides, the Lewis acidity has been studied by spectroscopy and other methods. [8][9][10][11][12][13][14][15] Although some advances have been made recently, a persistent problem spanning essentially all the methods is the sample specificity. Additionally, it was suggested that the closest to actual value of Lewis acidity, in theory, involves the calculation of the enthalpy change derived from the formation or dissociation of a Lewis acid-base pair in the vapor phase.…”
Section: Introductionmentioning
confidence: 99%